Identification of Andesite Resource Potential In Kalirejo Area, Kokap Sub-District, Kulon Progo Using Resistivity Method - Rizqi Prastowo; Hurien Helmi; Obrin Trianda; Rofiqul Umam (Universitas Muhammadiyah Surakarta, 2021)
In the last five years, the need for materials to build infrastructure in Kulon Progo Regency has increased with the construction of an international airport. In the construction process, strong earth or rock materials are needed to make buildings resistant to earthquakes, one of which is andesite rock. This study aims to determine andesite rocks' resources using a three-dimensional model based on the value of resistivity in Kalirejo district Kokap Kulon Progo. The research was conducted by geological and geophysical survey. Based on data on the distribution of rocks in the research area included in the intermediate igneous rocks, andesite. These rocks are intrusions that develop in research areas. Petrography analysis is used to determine the types of minerals in andesite rocks and determine which levels of rock changes have changed or not to affect the strength of rocks. These rocks are intrusions that develop in research areas. Geophysical survey is by resistivity method using configuration dipole-dipole with five lines, and each stretch is 200 m. Based on three-dimensional model resistivity, fresh andesite is at a depth of between 5-10 m. Value of andesite resistivity is more than 668 Ωm, while the value of weathered andesite resistivity ranges from 256-536 Ωm and andesite resources about 332,580 tons.